Resistin in cardiac diseases: from molecular mechanisms to clinical implications - Ling, Yicheng; Han, Baixue; Gu, Tianxiang; Jiang, Xuan (Frontiers in Endocrinology, 2025)
Resistin, a cysteine-rich adipokine, exhibits significant species-specific divergence in its cellular origins and pathophysiological functions. In humans, it is primarily secreted by monocytes, macrophages, and bone marrow-derived cells, positioning it as a pivotal mediator of inflammation and cardiometabolic disease rather than a direct regulator of glucose metabolism. This review synthesizes current evidence on the multifaceted role of resistin in cardiovascular pathophysiology, emphasizing its engagement with key receptors—toll-like receptor 4 (TLR4) and cyclase-associated protein-1 (CAP-1)—to activate downstream proinflammatory signaling cascades including nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways. These mechanisms promote endothelial dysfunction, increase leukocyte adhesion and migration, and accelerate early atherogenesis. Beyond the vasculature, resistin exerts direct detrimental effects on the myocardium by impairing cardiomyocyte calcium handling and mitochondrial energetics, inducing pathological hypertrophy, and stimulating cardiac fibrosis via JAK/STAT3 and transforming growth factor-beta (TGF-β) signaling. Its ability to modulate neurohormonal pathways, including sympathetic activation and interactions with the endocannabinoid system, further integrates resistin into a complex network that exacerbates hypertension, arrhythmogenesis, and adverse cardiac remodeling. Clinically, elevated circulating resistin levels are consistently associated with acute coronary syndromes, heart failure progression, and major adverse cardiovascular events, often providing prognostic value beyond traditional risk factors, particularly in heart failure with reduced ejection fraction and cardiometabolic disease. However, significant heterogeneity exists across populations due to comorbidities such as renal dysfunction, ethnic variations influenced by genetic polymorphisms, and disease-specific contexts. The translational potential of resistin as a therapeutic target is underscored by preclinical studies demonstrating that its suppression ameliorates cardiovascular injury, though causal evidence in humans remains limited. Future research must prioritize elucidating resistin’s full receptor signaling repertoire, defining isoform-specific functions, and validating its utility in multimodal biomarker panels to enhance risk stratification and pave the way for targeted therapies in cardiovascular diseases. This review advances the field by resolving conflicting receptor data through a critical evaluation of CAP-1 and TLR4 signaling, and by integrating clinical evidence with molecular mechanisms.